Impact of Religion on Food and Nutrition - Gowder , Sivakumar J T (Journal of Ecohumanism, 2024)
Food, shelter, and clothes are essential factors for human life. Food and nutrition are necessary for human health and well-being. Food is responsible for human growth, providing energy and developing the immune system, thereby protecting human health. Even we can treat 95% of diseases through proper and healthy food. Education on food and nutrition plays a crucial role in adopting a healthy lifestyle in this modern society. In addition to education, religion plays a vital role in food and nutrition, shaping our culture through cultural norms and ethical values. All religions have their dietary guidelines that are concerned with their religious significance. Religious fasting practices are helpful in keeping our bodies healthy through reliable metabolic activities. All religions preach to people about the importance of food sharing and the complications of wasting food. In this article, we can understand the role of religion on food and nutrition in our human society that can help health care professionals to provide common dietary guidelines that will be beneficial to our society.